2017
DOI: 10.1038/eye.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation and grading of ocular involvement in patients with Tessier number 10 clefts

Abstract: PurposeThe objective of this study is to evaluate and grade the extent and severity of ocular involvement in Tessier number 10 cleft.Patients and methodsA retrospective, noncomparative, interventional case series was conducted between January 2006 and December 2015. Clinical data were reviewed from 59 patients (85 eyes) with Tessier number 10 clefts. Detailed medical history and ophthalmic examination of patients with a confirmed diagnosis of Tessier number 10 cleft were recorded on an itemized data collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The ophthalmic features include eyebrow madarosis, abnormal hairline, upper eyelid coloboma, superior symblepharon, ocular surface keratinization, and anterior staphyloma. [ 14 15 ] In our study, we found that the madarosis was lateral in cleft 9 and medial in cleft 12.…”
Section: Discussionsupporting
confidence: 50%
“…The ophthalmic features include eyebrow madarosis, abnormal hairline, upper eyelid coloboma, superior symblepharon, ocular surface keratinization, and anterior staphyloma. [ 14 15 ] In our study, we found that the madarosis was lateral in cleft 9 and medial in cleft 12.…”
Section: Discussionsupporting
confidence: 50%
“…Shao et al [4] had published a classification and grading system of ocular involvement for Tessier cleft 10 patients, wherein the eyelid coloboma was graded from 0 to 3 (0, no upper eyelid defect; 1, less than 1/3rd eyelid defect; 2, greater than 1/3rd but less than 1/2 eyelid defect; 3, more than half eyelid defect); symblepharon and cutaneous pterygium were scored between 0 to 3 (0, no symblepharon; 1, symblepharon and cutaneous pterygium confined to the corneal limbus; 2, symblepharon and cutaneous pterygium extending up to the pupil margin; 3, symblepharon and cu-…”
Section: Isolated Unilateral Tessier Cleft 10 With Anterior Staphylomamentioning
confidence: 99%
“…The ocular abnormalities which are associated mainly include congenital ocular surface problems like symblepharon, cutaneous pterygium and corneal abnormalities like corneal neovascularization and keratinization [ 4 ]. In few cases lower eyelid ectropion has also been reported.…”
mentioning
confidence: 99%
See 2 more Smart Citations